2016
DOI: 10.1080/15384101.2016.1207838
|View full text |Cite
|
Sign up to set email alerts
|

Cdk3, a conjugation-specific cyclin-dependent kinase, is essential for the initiation of meiosis in Tetrahymena thermophila

Abstract: Meiosis is an important process in sexual reproduction. Meiosis initiation has been found to be highly diverse among species. In yeast, it has been established that cyclin-dependent kinases (Cdks) and cyclins are essential components in the meiosis initiation pathway. In this study, we identified 4 Cdks in the model ciliate, Tetrahymena thermophila, and we found one of them, Cdk3, which is specifically expressed during early conjugation, to be essential for meiosis initiation. Cdk3 deletion led to arrest at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…RNA was extracted, sequenced and mapped according to a method described previously (Yan et al, 2016a). Briefly, total RNA was extracted from WT cells at the starvation, co-stimulation and conjugation stages, and from ΔCDK19 and ΔCYC9 cells at the starvation (KO cells) and costimulation stages (KO cells and WT cells mixed in a ratio of 9:1 for 1 h) using the RNeasy Protect Cell Mini Kit (Qiagen), as previously described (TetraFGD: http://tfgd.ihb.ac.cn/) (Wuitschick et al, 2002).…”
Section: Transcriptome Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted, sequenced and mapped according to a method described previously (Yan et al, 2016a). Briefly, total RNA was extracted from WT cells at the starvation, co-stimulation and conjugation stages, and from ΔCDK19 and ΔCYC9 cells at the starvation (KO cells) and costimulation stages (KO cells and WT cells mixed in a ratio of 9:1 for 1 h) using the RNeasy Protect Cell Mini Kit (Qiagen), as previously described (TetraFGD: http://tfgd.ihb.ac.cn/) (Wuitschick et al, 2002).…”
Section: Transcriptome Analysismentioning
confidence: 99%
“…showed that T. thermophila has a total of 34 cyclins (Yan et al, 2016b), and only four standard CDKs with exact PSTAIRE-like cyclin-binding motifs (Yan et al, 2016a). Because of the divergence between the number of annotated cyclin and CDK genes in this organism, we searched for additional CDK family members and identified a total of 20 CDKs or CDK-like genes in the T. thermophila macronuclear genome (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…In Tetrahymena , previous examples of genes required for meiotic initiation and DSBs included meiosis-specific cell cycle regulators such as cyclins and CDKs, which act upstream of the process (43,44), but co-factors that support DSB formation by Spo11 have not yet been found. Here, we report that Pars11 has functions in DSB initiation and restriction and in DNA damage sensing.…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified other important meiotic regulators in T. thermophila, including the Cyc2 and Cyc17 cyclin and the Tcdk3 cyclin-dependent kinase [27,28]. To investigate the function of E2fl1/Dpl2 complex during meiosis regulation, we tracked the expression of meiotic genes in dpl2D and e2fl1D cells (Figure 3(A)) and used these data to construct a meiotic regulatory network (Figure 3(B)).…”
Section: T Thermophila Dpl2 and E2fl1 Form A Transcription Factor Comentioning
confidence: 99%
“…Cyc2 and Tcdk3 may act together to initiate meiosis. They regulated the expression of genes important for early prophase that functioned in DSBs formation and repair [28]. Cyc17 was essential for initiating meiotic anaphase and mainly regulated the genes involved in meiotic anaphase, including those that functioned in chromosome condensation and segregation [27].…”
Section: T Thermophila Dpl2 and E2fl1 Form A Transcription Factor Comentioning
confidence: 99%